Health Security Intelligence (Taylor & Francis, 2024)
The book takes a multi-disciplinary approach to explore the role national security intelligence agencies played in supporting national governments’ response to COVID-19. Spanning the ‘Five Eyes’ intelligence countries (UK, USA, Canada, Australia and New Zealand), this book offers the first cross-comparative analysis of what intelligence agencies need to focus on in responding more effectively to future emerging health and biological security threats risks and hazards post-COVID-19. The volume addresses three principal issues. First, it investigates what roles the Five Eyes intelligence communities played (along with other key stakeholders, such as public health agencies) in managing the COVID-19 pandemic. Second, it assesses the challenges of and lessons learnt from these intelligence communities’ engagement in managing aspects of the pandemic. Third, it explores how the Five Eyes might play more effective roles in managing future health security threats and risks, whether those are intentional (bioterrorism and bio crimes), accidental (laboratory releases) or unintentional (pandemics) in origin. Overall, this book offers a coherent and holistic research agenda that seeks to improve understanding about the role of national security intelligence in managing health security threats and risks post-COVID-19. This book will be of much interest to students of intelligence studies, health security, public health and International Relations. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.